"…Попливла, наче чорна лебідка" (метафоричний портрет жінки у прозі Юрія Винничука) - Сенькович, О. (Культура слова, 2019)
У статті констатовано, що твори сучасного автора Юрія
Винничука становлять знаковий фрагмент української художньої
прози кінця ХХ – початку ХХІ століття. На матеріалі романів
«Мальва Ланда» та «Весняні ігри» продемонстровано специфіку
індивідуального мовомислення прозаїка, зокрема у царині мовного
портретування жінки.
На підставі здійсненого розгляду стилістичних засобів мовно-
художнього портретування жінки у прозі Юрія Винничука виявлено
продуктивні способи метафоризації з використанням номінацій
птахів, рослин, предметів побуту тощо. The article states that the works of the contemporary author Yuri
Vynnychuk constitute a landmark fragment of Ukrainian prose of the late
twentieth – early twentieth centuries. The material of the novels «Malva
Landa» and «Spring Games» shows the specifics of individual linguistic
prose, in particular in the field of linguistic portraiture of a woman.
Based on the consideration of stylistic means of linguistic and artistic
portraiture of a woman in prose of Yuri Vynnychuk, productive ways of
metaphorization with the use of nominations of birds, plants, household
objects and so on were identified.
The specifics of the author’s development of the affectionate-poetic
names of women, which are characteristic of the Ukrainian folklore
tradition, are traced. These include the generic nomination bird and
specific nominations swallow, swallow, winch, winch, winch, winch,
turtle, cuckoo, quail, cuckoo, cuckoo. It was emphasized that despite
their trawliness, they did not lose their imagery and emotionality. Such
a contextual affectionate name of women is taken as a typical feature of
folklore by a modern reader.
Also actively portrayed and psycho-emotional descriptions of women
in associative juxtaposition with the traits of such birds as owl, crow,
canary, are actively presented in Yuri Vynnychuk’s prose.
An examination of stylistic means of linguistic and artistic portraiture
of a woman in prose by Yuriy Vynnychuk reveals productive ways of
metaphorizing using animal nominations and household items.